Plasmodium falciparum founder populations in western Cambodia have reduced artemisinin sensitivity in vitro. - Amaratunga, C; Witkowski, B; Dek, D; Try, V; Khim, N; Miotto, O; Ménard, D; Fairhurst, R (American Society for Microbiology, 2014)
Reduced Plasmodium falciparum sensitivity to short-course artemisinin (ART) monotherapy manifests as a long parasite clearance half-life. We recently defined three parasite founder populations with long half-lives in Pursat, western Cambodia, where reduced ART sensitivity is prevalent. Using the ring-stage survival assay, we show that these founder populations have reduced ART sensitivity in vitro at the early ring stage of parasite development and that a genetically admixed population contains subsets of parasites with normal or reduced ART sensitivity.